DEVELOPMENT PCR TEST FOR SPECIFIC IDENTIFICATION C. COLI, C. JEJUNI, C. FETUS - Shevtsov , A.B.; Kairzhanova , A.D.; Abisheva , G.D.; Shevtsova , E.S.; Kamalova , D.K.; Dzhailbekova , A.S.; Karibaev , T.B.; Sytnik , I.I.; Ahmetova , A.E.; Mukanov , K.K. (Eurasian Journal of Applied Biotechnology, 2014)
At this time, the laboratories responsible for diagnostics of campylobacteriosis and evaluation of the animal products contamination by campylobacteria use “golden standard” – extraction and identification of clean cultures. However, campylobacteria microaerophiles grow on complex growth medium and require high qualified staff. The diagnostics is also complicated due to diversity of clinical campylobacteriosis. As a result there is an underestimation of the true campylobacteriosis situation in the structure of the human and animal infectious diseases. Introduction of the PCR tests into diagnostic laboratories may simplify and increase the level of camplylobacteriosis infections diagnostics. The aim of the work was development of high PCR test for identification of species differentiation of C. coli, C. jejuni and C. fetus in clinical material and animal products. In the research the primers selected to the unique DNA markers Cc01460c for C. coli and Cj0339 for C. jejuni were used; for species differentiation of C. fetus primers for rpoB gene were selected. The conditions were optimized by real-time PCR using intercalating dye SybrGreen, which allowed evaluating the maximum efficiency on basis of minimum value of threshold cycle (Ct). As a result the protocol with optimized composition of reaction mixture and PCR amplification program was developed. Sensitivity evaluation on two-fold diluted DNA samples has allowed identifying analytical sensitivity threshold in 108 genomic equivalents for C. coli and C. fetus and 13.7 genomic equivalent for C. jejuni. The sensitivity evaluation of the PCR test on DNA of 10 camplylobacteria types, DNA of genetically related H. pylori, as well as DNA of the bacteria that cause human and animal infectious diseases similar to the clinical picture, has proved high test specificity. High analytical sensitivity and specificity allow to use the developed test in express diagnostics of campylobacteriosis as well as to analyze contamination of animal products by C. coli, C. fetus and C. jejuni.